RETRACTED: Measure and evaluate the hydrothermal flow of a Newtonian fluid in homogeneous permeable media equipped with a fin: A numerical approach - Bilal, Sardar; Khan, Noor Zeb; Riaz, Arshad; Alyami, Maryam Ahmed; El-Din, ElSayed M. Tag (Frontiers in Physics, 2022)
This document envisions hydrothermal characteristics of viscous fluid in homogenously permeable hexagonal enclosure. Permeability aspects in flow domain is described by employing Brinkman-extended Darcy law. Corrugated Hexagonal enclosure along with placement of star shaped fin is taken into account. Heated rectangular blocks at horizontal extremities are installed and sliding sides of enclosure is considered to be cold to provide convective potential to the flow. In addition, adjoining portions of heated rectangular blocks are supposed to be adiabatic. The dimensionless governing equations of resultant problem are derived initially and then solved numerically by implementing Galerkin finite element approach and COMSOL is obliged. For this purpose, firstly domain discretization is demonstrated in view of 2D elements by performing hybridized meshing. After then, system of non-linear equations is resolved by non-linear solver (PARADISO). Grid convergence test is performed to confirm credibility of carried simulations by calculating average Nusselt number at different refinement levels. Change in associated distributions against involved physical parameters (Darcy number (Da), Rayleigh number (Ra) and Prandtl number (Pr)) for wide range is revealed through graphs and tables. Quantities like kinetic energy, heat flux (local and average) are also evaluated through concerned parameters. The results clearly demonstrate that Darcy number tends to reduce heat transfer rate. In particular, it is depicted that by incrementing Rayleigh number (Ra) strengthening in temperature potential arises in the system therefore magnifies the heat transfer rate. Moreover, it is disclosed that by reducing Darcy number kinetic energy shows decreasing trend.